Economic Assessment of Microfinance in Women Empowerment in Bangladesh and Some Unsolved Judgments - Chowdhury, Farzana Yesmin (Asian Business Review, 2017)
This article provides a quantitative outcome evaluation of microfinance in women empowerment in Bangladesh. It first evaluated the economic assessment of microfinance which showed the positive outcome of the economic indicators. At the same time, it also underlines some persisting unresolved methodical issues as well as economic issues. This analysis reflects the economic significance along with limitations of the microfinance program in Bangladesh since its beginning in the 1980s, and it will make comfortable for the further critical analysis of the contribution of the microfinance in women empowerment in Bangladesh.